Нанокомпозити діоксидів кремнію, титану, цирконію і церію – загусники пластичних мастил - Borysenko, L. I.; Mnischenko, G. G.; Kulyk, K. S.; Petrus, L. V.; Sulim, I. Yа.; Borysenko, M. V. (Chuiko Institute of Surface Chemistry National Academy of Sciences of Ukraine, 2010)
Nanocomposites of MO2/SiO2 (M = Ti, Zr and Ce), prepared by molecular layering and impregnation methods, are investigated by X-ray diffraction analysis, thermogravimetry and low-temperature desorption of argon. MO2/SiO2, containing 5 % wt. MO2, were used as a thickener of greases based on polyethylsiloxane PES-5. These siloxane greases are distinguished by good mechanical stability and are efficient up to 200 °C.